Manufacturing method for D03 type Fe3Al particle powder

Fe-Al alloy particles are generated by a high-frequency magnetic field-driven thermal plasma method and heat treatment is performed, which solves the problem of industrial manufacturing of D03 type Fe-Al alloy materials in the prior art, and realizes low-cost, efficient preparation and excellent performance metal parts.

JP7649175B2Active Publication Date: 2025-03-19DOWA HOLDINGS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2021046666
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-19
Publication Date
2025-03-19
Estimated Expiration
2041-03-19

AI Technical Summary

Technical Problem

It is difficult to industrially manufacture Fe-Al alloy materials with a D03-type regular lattice structure, especially when preparing thin films or single crystal materials required for thermal fluid sensors and thermoelectric power generation equipment, there are problems of difficulty in material processing and high cost.

Method used

Metal vapor is generated by a thermal plasma method driven by a high frequency magnetic field, and condensed in rare gases to form Fe-Al alloy particles, followed by heat treatment to maintain the D03 type regular lattice structure, and the particle size and shape are adjusted to suit different application requirements.

Benefits of technology

The low-cost and efficient preparation of the D03 type Fe-Al alloy material is achieved, allowing easy processing into metal parts with a given shape and excellent performance in thermoelectric and sensor applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649175000006
    Figure 0007649175000006
  • Figure 0007649175000007
    Figure 0007649175000007
  • Figure 0007649175000008
    Figure 0007649175000008
Patent Text Reader

Abstract

To provide a raw material of a D03-type Fe3Al crystal for easy processing for a predetermined shape.SOLUTION: A manufacturing method of a D03-type Fe3Al particle powder includes: a metal particle synthesis step where a thermal plasma is generated by applying a high frequency magnetic field to an inert gas supplied to a high frequency coil, a metal vapor of Fe and Al is generated by supplying a powder raw material composed of Fe and Al to the thermal plasma, and the metal vapor is condensed in a gas phase composed of the inert gas to synthesize a metal particle of an Fe-Al alloy of which Fe and Al atomic ratio is in a range of 81.0:19.0 to 65.0:35.0; and an ordered lattice step where an Fe3Al phase having a D03 type ordered lattice structure is produced by heating and maintaining the metal particle at 300 to 625°C.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention is a method for producing Fe with a D03 type ordered lattice structure. 3 The present invention relates to a method for producing powder made of particles of an Al intermetallic compound. [Background technology]

[0002] Fe with a D03 type superlattice structure 3 Al intermetallic compounds are known to exhibit a large anomalous Nernst effect and are considered promising materials for constructing heat flow sensors and thermoelectric generation devices. 3 As examples of Al crystal production, Non-Patent Document 1 reports a thin film production example by molecular beam epitaxy method (MBE) and a single crystal production example by the Czochralski method (rotational pulling method).

[0003] Thermoelectric conversion elements for constructing heat flow sensors are required to have thicknesses on the order of several hundred nanometers or microns. Thermoelectric conversion elements for realizing thermoelectric generating devices are preferably bulk bodies with thicknesses of several millimeters. Film-forming techniques such as molecular beam epitaxy and sputtering can be used to prepare thin film samples on the order of several hundred nanometers, but are not suitable for D03-type Fe in terms of film-forming time and cost. 3 The Czochralski method is not suitable for industrially manufacturing large-sized D03-type Fe 3 It is possible to obtain Al single crystals. However, Fe 3 Al single crystal is very hard. Fe 3 It is extremely difficult to cut out elements of a given size from an Al single crystal, especially to obtain elements with thicknesses on the order of nanometers or microns. 3 It is also difficult to crush and powder the Al single crystal. Therefore, bulk D03 type Fe 3The technology for obtaining single crystal Al is also not suitable as a means for industrially producing elements of heat flow sensors or thermoelectric generation devices.

[0004] On the other hand, Non-Patent Document 2 shows an experiment in which Fe-Al alloy nanoparticles were produced by melting an Fe-Al alloy ingot with a hydrogen plasma arc, vaporizing it in a chamber, and then recovering the solidified powder. According to the description in this document, Fe with a D03 structure 3 However, the X-ray diffraction pattern using Cu-Kα radiation (Fig. 3) showed that Fe nanoparticles with the D03 structure were 3 Since no {200} peak (near 2θ=30.9°) specific to Al crystals was observed, the crystal structure of the Fe-Al alloy nanoparticles actually produced is not considered to be a D03 type ordered lattice structure, contrary to the description in the literature. It is presumed that particles mainly composed of an Fe-Al alloy phase with an irregular structure were produced. [Prior art documents] [Non-patent literature]

[0005] [Non-Patent Document 1] Akito Sakai et al. Iron-based binary ferromagnets for transverse thermoelectric conversion. Nature 581 (2020) 53-57. [Non-Patent Document 2] Tong Liu et al. Preparation and characteristics of Fe3Al nanoparticles by hydrogen plasma-metal reaction. Solid State Communications 125 (2003) 391-394. Summary of the Invention [Problem to be solved by the invention]

[0006] Until now, Fe with a D03 type ordered lattice structure has been 3 Al intermetallic compounds are available in the form of thin films or single crystals. However, as mentioned above, it is extremely difficult to industrially manufacture parts of a given shape using these thin film or single crystal materials. The present invention is a D03 type Fe alloy that is easy to process into parts of a given shape. 3 The purpose is to provide an Al crystal material. [Means for solving the problem]

[0007] The objective of the present invention is to obtain Fe-Al alloy particles with a composition in which the atomic ratio of Fe to Al is in the range of 81.0:19.0 to 65.0:35.0 by heating and holding at 300 to 625°C, and to obtain Fe with a D03 type ordered lattice structure. 3 D03 type Fe with "ordered lattice process" that generates Al phase 3 This is achieved by the manufacturing method of the Al particle powder. In addition, as a process for synthesizing metal particles of Fe-Al alloy to be subjected to the above-mentioned "ordered lattice process", a "metal particle synthesis process" can be adopted in which a high-frequency magnetic field is applied to a rare gas supplied into a high-frequency coil to generate thermal plasma, a powder raw material composed of Fe and Al is supplied into the thermal plasma to generate metal vapor of Fe and Al, and the metal vapor is condensed in a gas phase composed of the rare gas, thereby synthesizing metal particles of Fe-Al alloy having a composition in which the atomic ratio of Fe:Al is in the range from 81.0:19.0 to 65.0:35.0.

[0008] In the above-mentioned regular lattice forming process, the D03 type Fe 3 Fe with a D03 type superlattice structure, in which the intensity ratio I{111} / I{220} of the diffraction peak heights of the {111} and {220} planes of the Al superlattice is 0.005 or more. 3 It is preferable to form an Al phase. The heating and holding time at 300 to 625°C may be, for example, 5 to 300 minutes. It is more preferable to set the heating and holding temperature at 400 to 600°C.

[0009] The above D03 type Fe3 The size of the Al particle powder can be adjusted so that the average particle size based on the major axis is within the range of 20 to 500 nm, for example. Powder with such a small particle size is preferable in terms of lowering the sintering temperature. Effect of the Invention

[0010] According to the present invention, D03 type Fe 3 It is possible to obtain a powder composed of nanoparticles of Al crystals. Since the powder with a small particle size obtained by the present invention has a low sintering temperature, it is possible to obtain a powder composed of nanoparticles of Al crystals. 3 It is possible to easily fabricate metal parts of a given shape made of Al intermetallic compounds. In addition, by applying nanoimprint technology, it is possible to easily fabricate metal parts of a given shape made of Al intermetallic compounds. 3 It also becomes possible to form wiring of an Al intermetallic compound. [Brief description of the drawings]

[0011] [Figure 1] X-ray diffraction patterns using Co-Kα radiation for the test powders of Comparative Examples 1 and 2 and Examples 3, 2, 1, 4, and 5. [Diagram 2] X-ray diffraction patterns using Co-Kα radiation for the test powders of Comparative Examples 3 and 4 and Examples 6 and 7. [Diagram 3] 1 shows X-ray diffraction patterns using Co-Kα radiation for the powder of precursor particle C and the test powder of Example 8. [Figure 4] X-ray diffraction patterns using Co-Kα radiation for powders of precursor particles D, E, F, and G, and test powders of Examples 9, 10, 11, and 12. [Diagram 5] 1 shows X-ray diffraction patterns using Co-Kα radiation for the powder of precursor particle H and the test powder of Example 13. [Figure 6] 1 shows X-ray diffraction patterns using Co-Kα radiation for the powder of precursor particle I and the test powder of Example 14. [Figure 7] SEM photograph of precursor particle A powder. [Figure 8] SEM photograph of the test powder of Example 1. [Figure 9]SEM photograph of the test powder of Example 2. [Figure 10] SEM photograph of the test powder of Example 6. [Figure 11] SEM photograph of the test powder of Example 7. [Figure 12] SEM photograph of precursor particle D powder. [Figure 13] SEM photograph of precursor particle E powder. [Figure 14] SEM photograph of precursor particle G powder. [Figure 15] SEM photograph of precursor particle H powder. [Figure 16] SEM image of precursor particle I powder. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] As a result of the research, the inventors found that Fe 3 Fine particles of Fe-Al alloys with stoichiometric composition of Al or a composition slightly different from the stoichiometric composition are heated to about 500℃ and held there for a period of time, producing Fe with a D03 type superlattice structure. 3 In this study, we found that fine particles mainly composed of the Al phase can be obtained. In particular, the D03 type Fe 3 A manufacturing method is disclosed that combines the synthesis of Fe-Al alloy particles by a thermal plasma method and heat treatment, which is suitable for producing Al particle powder.

[0013] [Metal particle synthesis process] Fe-Al alloy particles are synthesized using the thermal plasma method. The thermal plasma method used here involves applying a high-frequency magnetic field to a rare gas supplied into a high-frequency coil to generate thermal plasma, supplying a powder raw material consisting of Fe and Al into the thermal plasma to generate metal vapor of Fe and Al, and condensing the metal vapor in a gas phase consisting of rare gas. The condensed phase (liquid phase) consisting of Fe and Al is immediately quenched and solidified, becoming solid particles of Fe-Al alloy. Ar, which is easily available, can be used as the rare gas.

[0014] The solid particles of Fe-Al alloys synthesized by the thermal plasma method still have the D03 type ordered lattice structure. 3 Therefore, the particles immediately after synthesis can be said to be precursor particles for forming an ordered lattice into a D03 structure in the "ordered lattice formation process" described later. According to the inventors' investigations, when the atomic ratio of Fe to Al in the precursor particles made of an Fe-Al alloy is in the range of 81.0:19.0 to 65.0:35.0, the crystal structure of the Fe-Al alloy precursor particles is a D03 type ordered lattice. 3 The phase of the FeAl intermetallic compound can be obtained. 3 The stoichiometric atomic ratio of Fe to Al in Al is 75.0:25.0, but in the above composition range around this, D03 type Fe exhibits a D03 type ordered lattice structure. 3 The D03 type FeAl particles can be obtained. 3 Al particles are Fe 3 This refers to particles of an Fe-Al alloy having an Al stoichiometric composition or a composition slightly deviated from that composition, and a powder made of these particles exhibits an X-ray diffraction pattern based on a regular lattice of a D03 type structure.

[0015] The form of the raw material applied to the thermal plasma method is preferably powder, since it is necessary to quickly become metal vapor by the thermal plasma. The composition of Fe and Al supplied by the raw material powder is set so that the composition of the precursor particles to be synthesized has an atomic ratio within the above range. The raw material powder may be a mixed powder consisting of pure Fe powder and pure Al powder, or a Fe-Al alloy powder of a predetermined composition manufactured in advance may be used. Depending on the manufacturing conditions of the device and the particle size of the raw material powder, a certain degree of variation may occur between the charged composition (i.e., the atomic ratio of Fe and Al supplied into the thermal plasma) and the composition of the precursor particles to be synthesized. By grasping the relationship between the composition and particle size of the raw material powder to be used and the composition of the particles to be synthesized through preliminary experiments, the composition of the precursor particles to be synthesized can be adjusted to the target composition. For example, in the thermal plasma device used in the examples described later, when the charged composition is set to 75.0:25.0 in terms of the atomic ratio of Fe and Al, the raw material has a cumulative 90% particle diameter D 90When Fe powder with a particle diameter of 6.8 μm and Al powder with a particle diameter of 36.8 μm were used, the atomic ratio of Fe to Al in the precursor particles (symbol B in Table 1) was 79.3:20.7. 90 When Fe powder with a particle size of 6.8 μm and Al powder with a particle size of 13.9 μm were used, the atomic ratio of Fe to Al in the precursor particles (symbol D in Table 1) obtained was 73.4:26.6.

[0016] [Regular grid formation process] The precursor particles collected from the thermal plasma device were subjected to heat treatment to produce Fe with a D03 type ordered lattice structure. 3 The Al phase was generated, and the "D03 type Fe 3 Al particles are obtained. D03 type Fe 3 In order to stably obtain Al particles, in the present invention, Fe-Al alloy particles (precursor particles) having an atomic ratio of Fe to Al in the range of 81.0:19.0 to 65.0:35.0 are subjected to heat treatment. The heat treatment can be performed by heating and holding the precursor particles at 300 to 625°C. The optimum holding time at that temperature can be found within the range of 5 to 300 minutes. In particular, it is more effective to hold the temperature in the range of 400 to 600°C, and more effective to hold the time in the range of 10 to 180 minutes. If the temperature is too low, if the heating holding time is too short, or if the temperature is too high, ordering into the D03 structure is not sufficiently achieved. If the heating holding time is too long, phase separation into the B2 structure (Fe-Al phase) and the bcc structure (α-Fe) tends to occur. The atmosphere during heating may be a non-oxidizing gas atmosphere or a vacuum. The vacuum atmosphere here means a state of pressure of 1 Pa or less.

[0017] [X-ray diffraction peak height intensity ratio] The Fe-Al alloy powder is called "D03 type Fe 3 Whether or not the powder is "Al particle" can be determined by measuring the X-ray diffraction (XRD) pattern of the powder using Cu-Kα or Co-Kα radiation. 3In the case of Al crystals, the {111} peak of the D03 type crystal is observed at a diffraction angle 2θ position where X-ray diffraction peaks of B2 type FeAl intermetallic compound crystals and α-Fe bcc crystals are not observed. The {111} peak of the D03 type crystal appears near 2θ = 26.7° when the X-ray source is Cu-Kα radiation, and near 2θ = 31.1° when the X-ray source is Co-Kα radiation. On the other hand, the D03 type Fe 3 The most intense X-ray diffraction peak of an Al crystal is the {220} peak, which appears near 2θ=44.2° when the X-ray source is Cu-Kα radiation, and near 2θ=51.9° when the X-ray source is Co-Kα radiation.

[0018] Here, the Fe 3 The Fe-Al alloy powder exhibits an X-ray diffraction pattern in which the intensity ratio I{111} / I{220} of the diffraction peak heights of the {111} and {220} planes in the Al superlattice is 0.005 or more. 3 It is judged that the powder is made of Al particles. In Fe-Al alloy powders with the intensity ratio I{111} / I{220} of 0.005 or more, it can be evaluated that the atomic arrangement of the ordered lattice has been highly ordered. Fe with a complete D03 structure 3 The calculated intensity ratio I{111} / I{220} in an Al superlattice is said to be 0.067 when the X-ray source is Cu-Kα radiation and 0.07 when the X-ray source is Co-Kα radiation, and is known to be roughly equivalent regardless of the X-ray source.

[0019] D03 type Fe 3 The {220} peak with the highest intensity of the Al crystal is close in diffraction angle 2θ to the {110} peak with the highest intensity of the B2 type FeAl crystal and the {110} peak with the highest intensity of the α-Fe crystal, so in X-ray diffraction patterns in which these peaks appear simultaneously, the peaks overlap each other. In such cases, the D03 type Fe 3 The peak intensity I{220} of the {220} plane of the Al crystal can be determined by taking the height of one of the superimposed peaks.

[0020] In the D03 type crystal, in addition to the above {111} peak, a {200} peak is also observed. D03 type Fe 3The {200} peak of Al crystals appears near 2θ=30.9° when the X-ray source is Cu-Kα radiation, and near 2θ=36.0° when the X-ray source is Co-Kα radiation. However, the position of this {200} peak is close to the position of the {100} peak of B2 type FeAl crystals. Therefore, the presence of the peaks near 2θ above alone is enough to identify D03 type Fe 3 Al crystals cannot be identified. D03 type Fe 3 In order to determine the formation of Al crystals, it is extremely effective to focus on the presence of the above-mentioned {111} peak that appears at a 2θ position that does not overlap with the diffraction peaks from the B2 type FeAl crystals or the disordered phase. 3 In the powder of Al particles, in addition to the above-mentioned intensity ratio I{111} / I{220} being 0.005 or more, it is more preferable that the intensity ratio I{200} / I{220} of the diffraction peak heights of the {200} plane and the {220} plane is also 0.005 or more.

[0021] Here, the peak intensity I{hkl} of the {hkl} plane in the X-ray diffraction pattern can be determined as follows. (How to determine the peak intensity I{hkl} of the {hkl} plane in an X-ray diffraction pattern) The X-ray diffraction pattern of the target powder is measured using Cu-Kα or Co-Kα radiation as the X-ray source. The peak intensity I{hkl} of the {hkl} plane is the maximum value I of the peak when measurement data in a specified range of 2θ including the background parts on both sides of the {hkl} peak is extracted and fitted by the least squares method using a pseudo-Voigt function f(2θ). The following formula can be used for the pseudo-Voigt function. In this case, the background is approximated as a straight line and expressed as A+B2θ. C is the normalization constant of the peak. n, m, and H are fitting parameters. The maximum value I of the peak is determined by the following formula (1).

number

[0022] The 2θ range for extracting data for determining I{hkl}, i.e., the above-mentioned "predetermined range including the background parts on both sides of the {hkl} peak", can be, for example, when using Co-Kα radiation as the X-ray source, the 2θ range for I{111} measurement can be 30 to 33°, the 2θ range for I{200} measurement can be 35 to 37°, and the 2θ range for I{220} measurement can be 50 to 55°. The following literature is useful for the analysis method of X-ray diffraction patterns by fitting using the pseudo-Voigt function. Reference: Hideho Toratani, "6. Profile Functions and Pattern Decomposition Methods", Journal of the Crystallographic Society of Japan 34, 86 (1992)

[0023] [Particle shape] The present invention's D03 type Fe 3 It is more preferable that the particles constituting the powder of Al particles are spherical. The spherical shape of the powder particles is advantageous in obtaining parts with fewer voids and other spaces and a high metal filling rate when the powder is sintered to produce metal parts. In addition, when the powder is applied to nanoimprint technology, it is advantageous in terms of fluidity. More specifically, it is desirable that the average circularity of the particles constituting the powder is 0.80 or more. In particular, it is more preferable that the average circularity is 0.85 or more for fine powders composed of nanoparticles. According to the manufacturing technology described below, spherical D03 type Fe 3 A powder composed of Al particles can be obtained. The average circularity can be determined as follows.

[0024] (How to calculate average circularity) The powder to be measured is observed with a SEM (scanning electron microscope), and all particles whose outlines can be seen in the SEM image of a randomly selected field of view are regarded as the particles to be measured. The circularity of each particle to be measured is calculated using the following formula (2). Circularity = 4πS / L 2 …(2) where S is the area of ​​the particle on the image (nm 2 ), L is the perimeter of the particle on the image (nm). The circularity measurement is performed on SEM images of one or more randomly selected fields of view so that the total number of particles to be measured is 50 or more, and the average circularity of the particles constituting the powder is determined by dividing the sum of the circularities of the individual particles by the total number of particles to be measured.

[0025] [Average particle size of powder] In the present invention, the particle size of the D03 type Fe 3 It is possible to obtain Al particle powder. For example, the average particle diameter based on the long diameter obtained from the SEM image is in the range of 20 to 500 nm. Such fine particle powder is advantageous in that the sintering temperature is low. From the viewpoint of low-temperature sintering, the average particle diameter is more preferably 20 to 200 nm, and may be controlled in the range of 50 to 150 nm. Here, the "long diameter" is the length of the long axis of an ellipse obtained by approximating the outline of the particle on the SEM image. However, if the ellipse is a perfect circle, it is the diameter of the circle. The average particle diameter can be obtained as follows.

[0026] (How to determine the average particle size) The powder to be measured is observed with a SEM (scanning electron microscope), and all particles whose outlines can be grasped in the SEM image of a randomly selected field of view are regarded as the particles to be measured, and the major axis of each particle to be measured is measured on the image. This major axis measurement is performed on SEM images of one or more randomly selected fields of view so that the total number of particles to be measured is 500 or more. A histogram of the major axis r of the particles to be measured is calculated using the following formula:

number

number

[0027] The particle size distribution can also be adjusted by classification or by mixing two or more types of powders with different average particle sizes. EXAMPLES

[0028] [Example 1] (Synthesis of precursor particles by thermal plasma method) Fe powder (manufactured by Kojundo Kagaku Kenkyusho Co., Ltd., D 90 = 6.8 μm) and Al powder (Kojundo Chemical Laboratory, D 90 =36.8μm) were weighed and mixed so that the atomic ratio of Fe:Al=70:30 to prepare a mixed powder as a raw material. Using a thermal plasma powder production apparatus equipped with an RF coil for generating thermal plasma and a water-cooled chamber for condensing metal vapor in the gas phase, a powder of Fe-Al alloy particles was produced by the thermal plasma method as follows. Ar gas was supplied to the above apparatus as a gas for generating plasma at a flow rate of 35NL / min, and a high-frequency current of a frequency of 13.56MHz was passed through the RF coil with an output of 6kW from a high-frequency power source, and a magnetic field was applied to the gas for generating plasma to generate Ar plasma. The above mixed powder as a raw material was supplied to the apparatus together with Ar gas as a carrier gas, and the mixed powder as a raw material was brought into contact with the plasma to make the mixed powder into a state of metal vapor. At this time, the supply rate of the mixed powder was 0.1 to 0.3g / min, the supply flow rate of the carrier gas was 5NL / min, and the pressure inside the apparatus was 100kPa. The metal vapor sent into the water-cooled chamber below the plasma generating section was quenched by the Ar gas in the chamber, condensed, and solidified as fine metal particles. The obtained metal particles were collected. These metal particles are called "precursor particles A." When the composition of precursor particles A was analyzed by EDX (energy dispersive X-ray analysis), the Fe:Al atomic ratio of the powder of precursor particles A was 76.7:23.3. The EDX device used was XFlash6130 manufactured by Bruker, which is attached to a SEM (scanning electron microscope) (the same applies to each of the following EDX analysis examples). In addition, the oxygen content was measured using an analyzer (EMGA-620W) manufactured by HORIBA, and was found to be 0.86% by mass. Figure 7 shows an example of an SEM (scanning electron microscope) photograph of the powder of precursor particle A. SEM observation was performed using a JEOL JSM-7800F (the same applies to each of the following examples). The length of the white scale bar shown near the bottom center of the photograph corresponds to 100 nm.

[0029] (Average particle size of precursor particles) According to the "How to calculate the average particle size" above, the average particle size was calculated from the images taken by SEM observation. The software used was "Origin 2020." The bin width was set to 30 nm, and the log-normal distribution function f(r) was fitted by the Levenberg-Marquardt method to determine the fitting parameters θ and μ. The average particle size was calculated based on these θ and μ. As a result, the average particle size of precursor particle A was determined to be 96 nm. (Average circularity of precursor particles) The average circularity of the precursor particles A was calculated according to the above-mentioned "Method of calculating the average circularity" and found to be 0.897. 2 was 0.00943. It has been confirmed that the particle shape and size are largely maintained even after the heat treatment described below.

[0030] (Heat treatment) The powder of precursor particle A was subjected to heat treatment in an Ar atmosphere at a holding temperature of 500° C. for 180 minutes. The heat treatment furnace used was an infrared gold image furnace (MILA-5000-PN, manufactured by Advance Riko Co., Ltd.) (the same applies to each of the following examples). The powder after this heat treatment was used as a test powder and subjected to the following experiment. An SEM photograph of the test powder of this example is shown in Figure 8. The length of the white scale bar shown near the bottom center of the photograph corresponds to 1 μm.

[0031] (X-ray diffraction intensity ratio of test powder) The X-ray diffraction pattern of the test powder was measured using an X-ray diffractometer (Malvern Panalytical, Empyrean) under the conditions of Co-Kα radiation, tube voltage 45 kV, and tube current 45 mA. Since the peaks due to Kα1 and Kα2 were superimposed in the obtained X-ray pattern, the peaks due to Kα2 were removed using the Rachinger method to obtain an X-ray diffraction pattern consisting only of peaks due to Kα1. At this time, the intensity ratio of Kα1 to Kα2 was set to Kα1 / Kα2=0.5, and calculations were performed using X-ray diffraction analysis software (Malvern Panalytical, HighScore Plus). For the X-ray diffraction pattern consisting only of peaks due to Kα1, a graph analysis software (Origin, OriginLab Corporation) was used to analyze the D03 type Fe 3 The heights of the diffraction peaks of the {111} and {220} planes of the Al crystal were measured, and the intensity ratio I{111} / I{220} of the diffraction peak heights of the {111} and {220} planes was calculated. Here, the 2θ range for I{111} measurement was 30 to 33°, and the 2θ range for I{220} measurement was 50 to 55°.

[0032] The X-ray diffraction pattern of the powder sample in this example is shown in Figure 1. The intensity ratio of the diffraction peak heights I{111} / I{220} in this example was 0.015, and the above heat treatment resulted in D03 type Fe. 3 It was confirmed that Al particles were obtained. In addition, a peak of the γ-Fe phase with an fcc structure was also observed in the X-ray diffraction pattern. This γ-Fe phase was generated when the metal vapor condensed in the thermal plasma method, but the peak intensity indicates that the amount of the mixed in was small (the same applies to the examples and comparative examples using the thermal plasma method described later). This type of heterophase is non-magnetic, so the small amount of mixed in is not thought to have a significant effect on the thermoelectric conversion properties.

[0033] (Composition of test powder) When measured by EDX (energy dispersive X-ray analysis), the atomic ratio of Fe to Al in the powder sample of this example was Fe:Al=76.6:23.4.

[0034] (Average particle size of test powder) According to the above-mentioned "Method of determining average particle size", the average particle size was determined in the same manner as in the case of the precursor powder, and the average particle size after the above heat treatment was 104 nm. (Average circularity of test powder) The average circularity was calculated according to the above-mentioned "Method of calculating the average circularity". The average circularity after the heat treatment was 0.897. 2 was 0.00654.

[0035] (Magnetic properties of test powder) The magnetic properties of the powder sample in this example were measured using a VSM (Quantum Design, DynaCool). The measurement conditions were: maximum applied magnetic field 2T, sweep speed 0.01T / sec, time constant 1sec, amplitude 2mm, and frequency 40kHz. At a temperature of 10K, the saturation magnetization was 123A·m 2 / kg, residual magnetization is 4.3 A m 2 / kg, coercivity is 7.8 kA / m (98 Oe), and the saturation magnetization at a temperature of 300 K is 111 A m 2 / kg, residual magnetization is 1.2 A m 2 / kg, coercive force is 0.95kA m 2 / kg (12 Oe).

[0036] Tables 1 and 2 summarize the main experimental conditions and results for each example in which precursor particles synthesized by the thermal plasma method were used.

[0037] [Example 2] The same experiment as in Example 1 was carried out, except that the heat treatment of the powder of precursor particles A was carried out for 10 minutes. An SEM photograph of the test powder of this example is shown in Figure 9. The length of the white scale bar shown near the bottom center of the photograph corresponds to 100 nm. The X-ray diffraction pattern of the powder sample in this example is shown in FIG. 1. The X-ray diffraction intensity ratio I{111} / I{220} in this example was 0.012, and it was confirmed that the D03 type Fe 3 It was confirmed that Al particles were obtained.

[0038] [Example 3] The same experiment as in Example 1 was carried out, except that the powder of precursor particles A was subjected to a heat treatment at a holding temperature of 450°C. The X-ray diffraction pattern of the powder sample in this example is shown in FIG. 1. The X-ray diffraction intensity ratio I{111} / I{220} in this example was 0.005, and the above heat treatment resulted in D03 type Fe. 3 It was confirmed that Al particles were obtained.

[0039] [Example 4] The same experiment as in Example 1 was carried out, except that the conditions for the heat treatment of the powder of precursor particles A were a holding temperature of 530° C. and a holding time of 10 minutes. The X-ray diffraction pattern of the powder sample in this example is shown in Figure 1. The X-ray diffraction intensity ratio I{111} / I{220} in this example was 0.011, confirming that D03 type Fe3Al particles were obtained by the above heat treatment.

[0040] [Example 5] The same experiment as in Example 1 was carried out, except that the conditions of the heat treatment applied to the powder of precursor particles A were a holding temperature of 600° C. and a holding time of 10 minutes. The X-ray diffraction pattern of the powder sample in this example is shown in Figure 1. The X-ray diffraction intensity ratio I{111} / I{220} in this example was 0.008, confirming that D03 type Fe3Al particles were obtained by the above heat treatment.

[0041] [Comparative Example 1] In this example, the same measurements as in Example 1 were carried out using the above precursor particle A powder (not subjected to heat treatment) as a test powder. The X-ray diffraction pattern of the powder sample (precursor particle A) is shown in Figure 1. 3 The {111} peak of Al crystals was not observed. In other words, the D03 type superlattice structure was not obtained when the particles generated by the thermal plasma method were not heat-treated.

[0042] [Comparative Example 2] The same experiment as in Example 1 was carried out, except that the conditions for the heat treatment of the powder of precursor particles A were a holding temperature of 200° C. and a holding time of 10 minutes. The X-ray diffraction pattern of the powder sample in this example is shown in Figure 1. When the heat treatment temperature was as low as 200°C, the D03 type ordered lattice structure was not obtained.

[0043] [Example 6] (Synthesis of precursor particles by thermal plasma method) Fe powder (manufactured by Kojundo Kagaku Kenkyusho Co., Ltd., D 90 = 6.8 μm) and Al powder (Kojundo Chemical Laboratory, D 90 =36.8μm) were weighed and mixed so that the atomic ratio of Fe:Al was 75:25 to prepare a mixed powder as a raw material. Using this mixed powder, metal particles were synthesized by a thermal plasma method under the same conditions as in Example 1. The metal particles obtained here are referred to as "precursor particles B". As a result of EDX analysis, the Fe:Al atomic ratio of the powder of precursor particles B was 79.3:20.7. Furthermore, when the specific surface area of ​​precursor particles B was measured by the BET single point method, it was found to be 6.38m 2 / g.

[0044] (Heat treatment) The powder of precursor particles B was subjected to a heat treatment in an Ar atmosphere at a holding temperature of 500° C. for a holding time of 10 minutes. The heat-treated powder was used as a test powder and subjected to the same experiment as in Example 1. An SEM photograph of the test powder of this example is shown in Figure 10. The length of the white scale bar shown near the bottom center of the photograph corresponds to 100 nm.

[0045] The X-ray diffraction pattern of the powder sample in this example is shown in FIG. 2. The X-ray diffraction intensity ratio I{111} / I{220} in this example was 0.005, and the above heat treatment resulted in D03 type Fe. 3 It was confirmed that Al particles were obtained.

[0046] [Example 7] The same experiment as in Example 6 was carried out, except that the heat treatment condition for the powder of precursor particle B was changed to a holding time of 180 minutes. An SEM photograph of the test powder of this example is shown in Figure 11. The length of the white scale bar shown near the bottom center of the photograph corresponds to 100 nm. The X-ray diffraction pattern of the powder sample (powder of precursor particle B) in this example is shown in FIG. 2. The X-ray diffraction intensity ratio I{111} / I{220} in this example was 0.007, and the above heat treatment was found to be a D03 type Fe 3 It was confirmed that Al particles were obtained.

[0047] [Comparative Example 3] In this example, the same measurements as in Example 6 were carried out using the powder of the precursor particles B (not subjected to heat treatment) as the test powder. The X-ray diffraction pattern of the powder sample in this example is shown in Figure 2. The {111} peak of the D03 type Fe3Al crystal was not observed. In other words, when the particles generated by the thermal plasma method were not subjected to heat treatment, the D03 type ordered lattice structure was not obtained.

[0048] [Comparative Example 4] The same experiment as in Example 6 was carried out, except that the powder of precursor particles B was subjected to a heat treatment at a holding temperature of 200°C. The X-ray diffraction pattern of the powder sample in this example is shown in Figure 2. When the heat treatment temperature was as low as 200°C, the D03 type ordered lattice structure was not obtained.

[0049] [Example 8] (Synthesis of precursor particles by thermal plasma method) Fe powder (manufactured by Kojundo Kagaku Kenkyusho Co., Ltd., D 90 = 6.8 μm) and Al powder (Kojundo Chemical Laboratory, D 90 = 36.8 μm) were weighed and mixed so that the atomic ratio of Fe:Al was 65:35 to prepare a mixed powder as a raw material. Using the mixed powder, metal particles were synthesized under the same conditions as in Example 1 by a thermal plasma method. The metal particles obtained here are referred to as "precursor particles C". As a result of EDX analysis, the atomic ratio of Fe to Al in the powder of precursor particles C was 72.3:27.7. The X-ray diffraction pattern of the powder of precursor particle C is shown in FIG.

[0050] (Heat treatment) The powder of precursor particles C was subjected to a heat treatment in an Ar atmosphere at a holding temperature of 500° C. for a holding time of 180 minutes. The heat-treated powder was used as a test powder and subjected to the same experiment as in Example 1.

[0051] The X-ray diffraction pattern of the powder sample in this example is shown in FIG. 3. The X-ray diffraction intensity ratio I{111} / I{220} in this example was 0.011, and the above heat treatment resulted in D03 type Fe. 3 It was confirmed that Al particles were obtained.

[0052] [Example 9] (Synthesis of precursor particles by thermal plasma method) Fe powder (manufactured by Kojundo Kagaku Kenkyusho Co., Ltd., D 90 = 6.8 μm) and Al powder (Kojundo Chemical Laboratory, D 90 =13.9μm) were weighed and mixed so that the atomic ratio of Fe:Al was 75:25 to prepare a mixed powder as a raw material. Using the mixed powder, metal particles were synthesized under the same conditions as in Example 1 by a thermal plasma method. The metal particles obtained here are referred to as "precursor particle D". As a result of EDX analysis, the atomic ratio of Fe to Al in the powder of precursor particle D, Fe:Al, was 73.4:26.6. 12 shows an example of an SEM photograph of the powder of precursor particle D. The length of the white scale bar shown near the center of the bottom of the photograph corresponds to 100 nm. The X-ray diffraction pattern of the powder of precursor particle D is shown in FIG.

[0053] (Heat treatment) The powder of precursor particles D was subjected to a heat treatment in an Ar atmosphere at a holding temperature of 500° C. for a holding time of 180 minutes. The heat-treated powder was used as a test powder and subjected to the same experiment as in Example 1.

[0054] The X-ray diffraction pattern of the powder sample in this example is shown in FIG. 4. The X-ray diffraction intensity ratio I{111} / I{220} in this example was 0.015, and the above heat treatment resulted in D03 type Fe. 3 It was confirmed that Al particles were obtained.

[0055] [Example 10] The same experiment as in Example 9 was carried out, except that in the synthesis of precursor particles by the thermal plasma method, Fe powder and Al powder were weighed and mixed so that the atomic ratio of Fe:Al was 70:30. The metal particles obtained here are called "precursor particles E". As a result of EDX analysis, the atomic ratio of Fe to Al in the powder of precursor particles E, Fe:Al, was 76.8:23.2. FIG. 13 shows an example of an SEM photograph of the powder of precursor particles E. The length of the white scale bar shown near the center of the bottom of the photograph corresponds to 100 nm. In addition, the X-ray diffraction patterns of the powder of precursor particles E and the test powder obtained by subjecting the powder of precursor particles E to heat treatment are shown in FIG. 4. In this example, the X-ray diffraction intensity ratio I{111} / I{220} was 0.012, and the heat treatment resulted in a D03-type Fe 3 It was confirmed that Al particles were obtained.

[0056] [Example 11] An experiment similar to that of Example 9 was carried out, except that in the synthesis of precursor particles by the thermal plasma method, Fe powder and Al powder were weighed and mixed so that the atomic ratio of Fe:Al was 68:32. The metal particles obtained here are called "precursor particles F". As a result of EDX analysis, the atomic ratio of Fe to Al in the powder of precursor particles F was 70.3:29.7. The X-ray diffraction pattern of the test powder obtained by subjecting the powder of precursor particles F to heat treatment is shown in FIG. 4. In this example, the X-ray diffraction intensity ratio I{111} / I{220} is 0.007, and the heat treatment results in a D03-type Fe 3 It was confirmed that Al particles were obtained.

[0057] [Example 12] The same experiment as in Example 9 was carried out, except that in the synthesis of precursor particles by the thermal plasma method, Fe powder and Al powder were weighed and mixed so that the atomic ratio of Fe:Al was 65:35. The metal particles obtained here are called "precursor particles G". As a result of EDX analysis, the atomic ratio of Fe to Al in the powder of precursor particles G was 68.3:31.7. FIG. 14 shows an example of an SEM photograph of the powder of precursor particles G. The length of the white scale bar shown near the center of the bottom of the photograph corresponds to 1 μm. In addition, the X-ray diffraction patterns of the powder of precursor particles G and the test powder obtained by subjecting the powder of precursor particles G to heat treatment are shown in FIG. 4. In this example, the X-ray diffraction intensity ratio I{111} / I{220} is 0.007, and the heat treatment results in a D03-type Fe 3 It was confirmed that Al particles were obtained.

[0058] [Example 13] In the synthesis of precursor particles by the thermal plasma method, the gas used was changed from Ar gas to Ar:H 2 The same experiment as in Example 9 was carried out, except that the mixed gas was changed to a volume ratio of 99:1. The metal particles obtained here are called "precursor particles H". As a result of EDX analysis, the atomic ratio of Fe to Al in the powder of precursor particles H was 76.4:23.6. FIG. 15 shows an example of an SEM photograph of the powder of precursor particles H. The length of the white scale bar shown near the center of the bottom of the photograph corresponds to 100 nm. In addition, the X-ray diffraction patterns of the powder of precursor particles H and the test powder obtained by subjecting the powder of precursor particles H to heat treatment are shown in FIG. 5. In this example, the X-ray diffraction intensity ratio I{111} / I{220} is 0.018, and the heat treatment results in a D03-type Fe 3 It was confirmed that Al particles were obtained.

[0059] [Example 14] (Preparation of raw powder by gas atomization method and synthesis of precursor particles by thermal plasma method) A wire cut product (manufactured by JFE Steel Corporation, diameter 5.5 mm × length 10 mm, purity 99.9% or higher) was prepared as the Fe raw material. Shot-like particles (manufactured by Kojundo Chemical Laboratory, particle size 5-10 mm, purity 99.99% or higher) were prepared as the Al raw material. These Fe raw materials and Al raw materials were weighed and mixed so that the atomic ratio was Fe:Al = 75:25. This mixture was placed in a water-cooled copper crucible with a diameter of 80 mm and heated at 1500 °C for 15 minutes by high-frequency induction heating to obtain Fe. 3 Molten Al alloy was produced. A boron nitride nozzle (inner diameter 2 mm) was used to extrude the molten metal from the nozzle into a gas phase space, and metal particles were synthesized by the gas atomization method in which Ar gas was sprayed onto the extruded molten metal. The gas nozzle diameter was φ40 mm, the gas spray pressure was 6 MPa, and the spray angle was 15°. The obtained metal particles were collected and classified using a sieve with a mesh size of 20 μm to extract fine particles. The composition of the powder consisting of the extracted particles was analyzed by SEM-EDX, and the molar ratio of Fe to Al, Fe:Al, was 75.0:25.0. The average circularity of the extracted particles was 0.893, and the circularity variance σ 2 was 0.0161. The powder consisting of these extracted particles was used as the raw material powder to synthesize metal particles by a thermal plasma method under the same conditions as in Example 9. The metal particles obtained here are called "precursor particles I." As a result of EDX analysis, the atomic ratio of Fe to Al in the powder of precursor particles I was 73.2:26.8. 16 shows an example of an SEM photograph of the powder of precursor particles I. The length of the white scale bar shown near the center of the bottom of the photograph corresponds to 100 nm. The X-ray diffraction pattern of the powder of precursor particles I is shown in FIG.

[0060] (Heat treatment) The powder of precursor particles I was subjected to a heat treatment in an Ar atmosphere at a holding temperature of 500° C. for a holding time of 180 minutes. The heat-treated powder was used as a test powder and subjected to the same experiment as in Example 1.

[0061] The X-ray diffraction pattern of the powder sample in this example is shown in FIG. 6. The X-ray diffraction intensity ratio I{111} / I{220} in this example was 0.013, and the above heat treatment resulted in D03 type Fe. 3 It was confirmed that Al particles were obtained.

[0062] [Table 1]

[0063] [Table 2]

Claims

1. a metal particle synthesis step in which a high-frequency magnetic field is applied to a rare gas supplied into a high-frequency coil to generate a thermal plasma, a powder raw material composed of Fe and Al is supplied into the thermal plasma to generate a metal vapor of Fe and Al, and the metal vapor is condensed in a gas phase composed of the rare gas to synthesize metal particles of an Fe-Al alloy having an atomic ratio of Fe:Al in the range of 81.0:19.0 to 65.0:35.0; By heating and holding the metal particles at 300 to 625° C., it is possible to obtain Fe 3 Al having a D03 type ordered lattice structure, in which the intensity ratio I{111} / I{220} of the diffraction peak heights of the {111} plane and the {220} plane of the D03 type Fe 3 Al ordered lattice in an X-ray diffraction pattern is 0.005 or more. 3 A superlattice forming step for generating an Al phase; D03 type Fe 3 A method for producing Al particle powder.

2. The D03 type Fe according to claim 1, wherein the heating and holding temperature is 400 to 600° C. in the ordering step. 3 A method for producing Al particle powder.

3. The D03 type Fe according to claim 1 or 2, wherein in the superlattice forming step, a particle powder having an average particle diameter of 20 to 500 nm based on the long axis is obtained. 3 A method for producing Al particle powder.